The Validity and Credibility of Tafsir Bi Al-Ma'tsur - Muhammad Shobirin; Muhammad Zia Ulhaq Albana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Tafsir bi al-ma'tsur is the oldest interpretation that is believed to be accurate and is a pillar as a basis for interpretation for the development of Qur'an interpretation in the future. It is because of this assumption that this study is here to prove the concentration of validity of this historical interpretation. The purpose of this study is to contribute to strengthening the reason for the tafsir bi al-ma'tsur as mashadir al-ashliyyah and explain the credibility of its interpreter. This study uses a qualitative method with a library research approach. The results of this study found that the tafsir bi al-ma'tsur is indeed clear of its validity. The interpretation of the Qur'an with the Qur'an which is the same verse explaining to each other, the interpretation of the Qur'an with the sunnah of the Prophet because he is indeed the Mubayyin of the Qur'an, the interpretation of the Qur'an with the qoul of the companions they sat with the Prophet when the revelation descended, the interpretation of the Qur'an with the aqwal tabi'in whose controversy oversees the interpretation so that it is sourced from the real mashadir al-ashliyyah, and the interpretation of the Qur'an with linguistic rules to dive into the meaning that the Qur'an is aimed at.